Discipline and Work Environment: A Strategic Combination in Enhancing Employee Performance at PT Rhino Indonesia - Muhammad Nazarudin; Asep Jamaludin; Nandang Nandang (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study aims to analyze the influence of work discipline (X1) and work environment (X2) on employee performance (Y) at PT Rhino Indonesia. A quantitative approach was employed using multiple linear regression analysis. The study involved a population of 160 employees, with a sample of 114 respondents determined using the Slovin formula. The partial t-test results indicate that both work discipline and work environment have a significant influence on employee performance. The simultaneous F-test results reveal that these two variables together significantly affect employee performance. The coefficient of determination (R Square) of 0.821 suggests that work discipline and work environment explain 82.1% of the variation in employee performance. The implication of this research highlights the importance for companies to enhance work discipline and foster a better work environment to improve employee performance. Furthermore, this study opens opportunities for future research on other factors that may influence employee performance.